Pengembangan Perangkat Lunak Pembangkit Geometri Fraktal Berbasis Bilangan Kompleks (PLFraKom) - Jaidan Jauhari (Fakultas Ilmu Komputer, Universitas Sriwijaya, 2010)
In fractal geometry, object is drawn using iterative algorithm. Fractal has self similarity by nature, such that each part of fractal is similar to the bigger part, but in different scale. Fractal generation process is done by iteration toward certain mathematic function. One of the mathematic function is the complex number-based one. The methodology used in developing this software is waterfall model. The design used functional model, that is DFD (Data Flow Diagram). PLFraKom software is developed in Microsoft Windows programming environment. Programming language used here is Borland C++ Builder 6.0. This software has produce the desired output, such as fractal image generation.